Determinants of Minimum Audit Fee Compliance: - Karim, Md. Rezaul; Sharif, Md. Jamil; Khasnobish, Tama Lika (Journal of Accounting, Business and Management (JABM), 2025)
This research investigates firm-specific determinants of minimum audit fee compliance (MAFC) of the listed companies in Bangladesh. MAFC is measured using a dichotomous variable of 1 if a firm complies with the minimum audit fee (MAF) guideline and 0 otherwise. Data used in this study are collected from the companies’ annual and corporate governance reports and analyzed using the logistic regression model. By utilizing 688 firm-year observations from 2016 to 2023, we find that firm size, cashflows, profitability, and directors’ ownership are the significant determinants of MAFC. Nevertheless, leverage, age, and board independence are found insignificant determinants of MAFC which contradicts prior findings as corporate governance system is weak in Bangladesh. The findings can be underpinned by the agency and legitimacy theories. This study can contribute largely to the economic and theoretical advancement of the body of existing literature with policy implications for regulators, auditors and firms as the literature on MAF is scarce. To the author’s knowledge, this is the first study on minimum audit fees from a quantitative perspective from the unique regulatory setting of Bangladesh.